2017
DOI: 10.1371/journal.pone.0184418
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the WNT5A-mimicking peptide Foxy-5 effectively reduces the metastatic spread of WNT5A-low prostate cancer cells in an orthotopic mouse model

Abstract: Prostate cancer patients with high WNT5A expression in their tumors have been shown to have more favorable prognosis than those with low WNT5A expression. This suggests that reconstitution of Wnt5a in low WNT5A-expressing tumors might be an attractive therapeutic approach. To explore this idea, we have in the present study used Foxy-5, a WNT5A mimicking peptide, to investigate its impact on primary tumor and metastasis in vivo and on prostate cancer cell viability, apoptosis and invasion in vitro. We used an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…The present study is the first to illustrate that inhibition of esophageal cancer cells using a CXCL antagonist may occur via inhibition of the PI3K/AKT signaling pathway. Previous studies have indicated that cell proliferation is strongly associated with cell apoptosis in the development of numerous types of cancer (31)(32)(33)(34)(35). In the present study, a reduction in cell proliferation was accompanied by increased apoptosis following treatment with UNBS5162, as determined by CCK-8 assays, flow cytometry and alterations in the expression of apoptosis-associated proteins.…”
Section: Discussionsupporting
confidence: 68%
“…The present study is the first to illustrate that inhibition of esophageal cancer cells using a CXCL antagonist may occur via inhibition of the PI3K/AKT signaling pathway. Previous studies have indicated that cell proliferation is strongly associated with cell apoptosis in the development of numerous types of cancer (31)(32)(33)(34)(35). In the present study, a reduction in cell proliferation was accompanied by increased apoptosis following treatment with UNBS5162, as determined by CCK-8 assays, flow cytometry and alterations in the expression of apoptosis-associated proteins.…”
Section: Discussionsupporting
confidence: 68%
“…Foxy-5 is a hexapeptide mimic of Wnt5a which is synthesized to possess Wnt5a-like properties that can impair cancer cell migration. After a successful phase 1 study in colon/breast/prostate cancer patients showing no toxicity, phase 1b trials are ongoing and expected to show promising therapeutic value (112). Also, peptides derived by modifying the Wnt5a ligand sequence have shown the capability to mimic the Wnt5a molecule.…”
Section: Wnt5a Mimeticsmentioning
confidence: 99%
“…Preclinical data show the involvement of both canonical and non-canonical WNT signaling in prostate cancer. A tumor-suppressive role has also been described for some members of the WNT pathway and early clinical studies are currently ongoing in different indications including metastatic prostate cancer to evaluate a peptide mimetic of WNT-5A which showed promising results in an orthotopic prostate cancer mouse model [ 74 ]. Deregulation of both the PI3K and WNT pathways further enhances prostate tumor growth due to aberrant downstream mTOR signaling [ 75 ].…”
Section: Treatment Options and Potential Novel Therapiesmentioning
confidence: 99%